Applying public health education at Riley County Health Department: a field experience report - Simpson, Makenzie (My University, 2014)
This is a report of field experience completed at the Riley County Health Department (RCHD) in Manhattan, KS. Under the supervision of Linda Redding RN, BSN, MPH and Patti Grub RN, two-hundred and forty hours of field experience were completed between January 13, 2014 and March 13, 2014. During the field experience, there was a variety of activities including developing a template for a monthly newsletter, attending meetings, shadowing staff in other departments, and working with Mrs. Grub on the disease investigations presented to the health department. The purpose of the field experience was to understand public health from the perspective of a local health department as well completing a report on tuberculosis, which was completed to know more about the disease itself.
Keywords: Riley County Kansas; Health Department; Public Health (0573)